THE DETERMINANTS OF HOUSEHOLDS POVERTY IN INDONESIA: Case Study of Individual in Household of Indonesia Family Live Survey (IFLS) - Andika Dwi Prasetya (EKPI 16 UMY 222, 2016)
This research examines the determinants of households poverty in Indonesia. Those determinant factors are Poverty, Occupation, Education, Sex, and Marital Status. This study employs the data of Indonesia Family Live Survey (ILFS) on 2007. The subject of research is the individual of households within age of 15 or more in 13 provinces of survey members. The methodology used in this research is Odds Ratio Method with STATA 11 SE. The results show that Education and Occupation influence the households poverty in Indonesia. Meanwhile, the other determinant factors, such as, sex, and marital status has no impact towards the determinant of households poverty in Indonesia. Keywords: Indonesia Family Live Survey (IFLS), Poverty, Odds Ratio